2006
DOI: 10.1179/acb.2006.033
|View full text |Cite
|
Sign up to set email alerts
|

A Survey on Alcohol and Illicit Drug Abuse Among Emergency Department Patients

Abstract: Alcohol and illicit drug abuse are major health care problems frequently leading to emergency department admission. The aims of this survey were (1) to determine for the Ghent University Hospital how frequently substance abuse contributed to emergency department admissions, (2) to describe the most important clinical features of these patients and (3) to determine how frequently these patients were referred to appropriate psychiatric services. All 1,941 patients attending the emergency department during the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 23 publications
1
19
0
1
Order By: Relevance
“…2,3,5 In a Belgian study conducted in a emergency unit, 2 three-fourths of the intoxicated patients suffered from alcohol abuse only, which is in line with the proportion of patients in our study, some of whom had concomitant substance abuse. In contrast, the proportion of cases involving only drug use was half of what was observed in our study.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…2,3,5 In a Belgian study conducted in a emergency unit, 2 three-fourths of the intoxicated patients suffered from alcohol abuse only, which is in line with the proportion of patients in our study, some of whom had concomitant substance abuse. In contrast, the proportion of cases involving only drug use was half of what was observed in our study.…”
Section: Discussionsupporting
confidence: 75%
“…Studies indicate that the number of people drinking to a level of intoxication that requires admission to a hospital seems to have been increasing over the last decade. [1][2][3][4][5][6] This behavior can lead to injuries, to physical violence and other aggressive behavior, and to suicidal behavior, as well as to other social and psychological problems. 7 In many cases that require emergency medical assistance, paramedics must initiate emergency care on site.…”
Section: Introductionmentioning
confidence: 99%
“…Also in studies from medical acute care settings, physicians have been asked to judge if the patient had been taking any substances recently (123)(124)(125). When compared with laboratory findings, most studies report significant discrepancies, whereas a few reported better agreement (126,127).…”
Section: Physician Assessmentmentioning
confidence: 99%
“…Although there appears to be an increased use of alcohol, it is not clear whether this also occurs with the abuse and misuse of prescription drugs. 4,5 Poison centers are available throughout the United States 24 hours a day. Calls from more than 2.4 million patients per year are documented in a database, providing a data set that captures information from a large geographic area and a wide ranging group of socioeconomic strata and ethnic groups.…”
Section: Introductionmentioning
confidence: 99%